Addressing physical skills and mental health: the role of modern teaching approaches in non-athlete university PE programs - Aslam, Sumaira; Shi, Yongbin; Zhao, Chen (Frontiers in Psychology, 2025)
BackgroundNon-athlete university students often face limitations in developing physical skills due to traditional physical education (PE) teaching methods. Additionally, mental health issues like depression and anxiety are common among this group, and physical inactivity may worsen these problems, leading to chronic conditions such as cardiovascular diseases and diabetes. This research seeks to assess the effects of various PE teaching strategies on physical skill development and mental health outcomes, including depression and anxiety, among non-athlete University students in Henan Province.MethodsA hybrid method approach was employed, involving a stratified random sample of 220 students (116 male, 104 female, mean age, 20) and 16 physical education professors. Quantitative data were collected using a validated 35-item questionnaire (Cronbach’s α = 0.971) and structured observational checklists. Qualitative data were gathered through semi-structured interviews. Data was analyzed using SPSS 29.0 and NVivo 12. Student-centered teaching strategies, including cooperative learning (β = 3.802, p = 0.002) and peer teaching (β = 3.838, p = 0.002).ResultsThe study found a 22% improvement in physical skill competence and reductions in mental health issues, such as anxiety and depression. In contrast, traditional direct instructions yielded minimal impact. Institutional challenges, including large class sizes and obsolete facilities, hindered optimal implementation.ConclusionThis study highlights the efficacy of Student-centered teaching strategies in both enhancing physical skills and mental health outcomes among non-athlete students. It underscores the need to address institutional limitations for more effective (PE) programs and chronic disease prevention.